Keanekaragaman Jenis Serangga di Perkebunan Kakao Desa Sejahtera Kecamatan Palolo Kabupaten Sigi - Hikma Abia; Fatma Dhafir; Masrianih; Vita Indri Febriani; Bustamin; Manap Trianto (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This research aims to determine the level of insect species diversity in the cocoa plantations of Sejahtera village, Palolo subdistrict, Sigi regency. The study was conducted on November 25–26 2025, using a quantitative descriptive method. Insect sampling was carried out using pitfall traps, light traps, sweeping nets, and hand collection techniques at three observation stations: areas around settlements, areas around rivers, and highland areas. The data obtained were analyzed using the Shannon–Wiener diversity index (H’). The results showed that a total of 223 insects were found consisting of 17 species, 12 families, and 8 orders. Insect species found include Oberea atropunctata, Amata prepuncta, Leptosia nina, Valanga nigricornis, Ischnura hastata, Dorcus parallelipipedus, Utetheisa pulchella, Amphiareus obscuriceps, Nyctemera baulus, Xysticus sp., Leptogenys diminuta, Oecophylla smaragdina, Diceroprocta vitripennis, Melanitis phedima, Calobatina geometra, Eurema sp., and Solenopsis sp. The overall insect species diversity index value is H’ = 2.37 which is classified as moderate. The results of this study are expected to provide basic information for communities and farmers in understanding the existence and role of insects, so that they can support more effective and sustainable cocoa plantation management.